2017
DOI: 10.22490/21456453.1843
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradación estimulada de los suelos contaminados con pesticidas organoclorados

Abstract: ResumenDDT al igual que otros pesticidas organoclorados han sido utilizados extensivamente en Colombia entre los años 1970 y 1980 en cultivos de algodón. DDT es resistente a la degradación y fuertemente relacionado con numerosos problemas de salud y actualmente está prohibido su uso. El propósito de esta investigación fue evaluar la biodegradación de DDT y de los productos DDD y DDE, presentes en el suelo contaminado durante 16 años en le municipio Agustín Codazzi, Cesar, Colombia. Se llevaron a cabo bioestimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
2
Order By: Relevance
“…The Figure 1 shows the existences of DDT in Latin America. Despite the organochlored pesticides, like DDT inhibit growth of microorganisms, and therefore is difficult their degradation, after long time permanence of these substance in soil, microorganisms may develop adaptation to them and use them like resource of primary carbon [3]. Sometimes the effects of pesticides on microbiota not always are negative, since after the application of an herbicide, for example, could increase the size of some group of microorganisms [43].…”
Section: Pesticides Higly Used In Colombiamentioning
confidence: 99%
See 1 more Smart Citation
“…The Figure 1 shows the existences of DDT in Latin America. Despite the organochlored pesticides, like DDT inhibit growth of microorganisms, and therefore is difficult their degradation, after long time permanence of these substance in soil, microorganisms may develop adaptation to them and use them like resource of primary carbon [3]. Sometimes the effects of pesticides on microbiota not always are negative, since after the application of an herbicide, for example, could increase the size of some group of microorganisms [43].…”
Section: Pesticides Higly Used In Colombiamentioning
confidence: 99%
“…The investigation was made near the city of Cartagena, also at the north of Colombia. In a region at the north of Colombia, where are cotton's cultures, Kopytko et al (2017) [3] shown in their research, that bacterial genera like Pseudomonas, Burkholderia, Aeromonas and Bacillus are proficient in processes bioaugmentation in order to obtain degradation of DDT.…”
Section: Pesticides Higly Used In Colombiamentioning
confidence: 99%
“…In the municipality of Codazzi (Cesar), large quantities of chemical inputs have been used in cotton crops for several years. In a study conducted by Kopytko et al (2017) Vibrio diabolicus A1S was isolated and its production of bioactive metabolites was evaluated with biodegradable polyhydroxybutyrate (PHB) polymer. This material has plastic-like characteristics and has potential applications in different industries.…”
Section: Bioremediation In Colombiamentioning
confidence: 99%
“…En este estudio se determinó que el pH fue la variable que tuvo mayor influencia sobre la biosorción de los metales evaluados. El uso de medios de cultivo con pH ácidos (pH entre 3 y 5) estimula la interacción iónica entre los metales y los grupos funcionales presentes en las paredes de las bacterias favoreciendo la adsorción de los mismos (Shakibaie, Khosravan, Frahmand, & Zare, 2008) (Bai et al, 2013) (Godleads, Tawari, Eruke, & Ehinomen, 2015) (Kopytko, Correa, & Estévez, 2017).…”
Section: Biorremediación Bacteriana De Metales Pesadosunclassified